Do different incision techniques for implant surgery affect gingival papilla height around dental implants? A retrospective study of 115 cases - Chenchen Luo; Ming Chen (BMC, 2023)
Abstract Background Surgical incision designs are considered closely correlated to gingival papilla of dental implants. This study aims to explore whether different incision techniques for implant placement and second stage surgery affect gingival papilla height. Methods Cases using different incision techniques (intrasulcular incisions or papilla sparing incisions) between November 2017 and December 2020 were selected and analyzed. A digital camera was used to capture images of gingival papilla at different time points. Ratio of papilla height to crown length using different incision techniques were measured and statistically compared. Results A total of 115 papillae (68 patients) were eligible according to the inclusion/exclusion criteria. The average age was 39.6 years. Decreased postoperative papilla height were observed after implant placement surgery in all groups without statistical difference. However, for second stage surgery, intrasulcular incisions lead to more atrophy in gingival papilla compared to papilla sparing incisions. Conclusions Selection of incision techniques in implant placement surgery does not significantly affect papilla height. For second stage surgery, intrasulcular incisions significantly leads to more papilla atrophy compared with papilla sparing incisions. Trial registration KQCL2017003.